MARS-F modeling of post-disruption runaway beam loss by magnetohydrodynamic instabilities in DIII-D. (11th October 2019) - Liu, Y.Q.; Parks, P.B.; Paz-Soldan, C.; Kim, C.; Lao, L.L.
Abstract: A drift orbit model for relativistic test electrons has been incorporated into the MARS-F code (Liu et al 2000 Phys. Plasmas 7 3681), in order to study the runaway electron (RE) behavior in the presence of magneto-hydrodynamic perturbations computed by MARS-F. By implementing the model directly into the MARS-F curve-linear magnetic coordinates, maximal accuracy in representing the full field perturbation is preserved. The updated code is utilized to study the high current RE beam loss in a post-disruption DIII-D plasma, revealing that a fast growing, n = 1 ( n is the toroidal mode number) resistive kink instability, at ̃100 Gauss level, can induce significant fraction of RE loss, largely by perturbing drift orbits of REs. A ̃1000 Gauss perturbation fully terminates the RE beam, as found in both experiment and modeling. The 3D field induced loss increases with the perturbation amplitude but decreases with the particle energy. The loss fraction is generally not sensitive to the initial particle pitch angle. The particle velocity change, due to electric field acceleration/deceleration, small pitch angle scattering, synchrotron radiation and Bremsstrahlung, further perturbs the RE trajectory but plays a minor role in prompt RE loss within microseconds time scale. Therefore, the dominant dependencies are simply the RE energy and instability strength. For comparison, a resonant magnetic perturbation field, generated by 4 kAt n = 3 even parity I-coil currents in DIII-D and with the plasma response field included, is found to induce almost no loss for the same RE beam.